Genome-Wide Profiling of Cardinium-Responsive MicroRNAs in the Exotic Whitefly, Bemisia tabaci (Gennadius) Biotype Q - Li, Hongran; Wei, Xiaoying; Ding, Tianbo; Chu, Dong (Frontiers in Physiology, 2018)
Although the bacterial symbiont Cardinium has profound effects on the ecological adaptation of its host, the whitefly Bemisia tabaci (Gennadius) biotype Q (hereafter referred to as B. tabaci Q), the molecular mechanism underlying interactions between these two organisms is not yet fully understood. In this study, sRNA libraries were constructed, amplified, and sequenced for Cardinium-infected (C+) and uninfected (C∗−) B. tabaci Q with identical genetic backgrounds. Subsequently, the genes targeted by the differentially expressed miRNAs were predicted by integrating the B. tabaci Q genome data. A total of 125 known and 100 novel miRNAs were identified, among which 23 significant differentially expressed miRNAs were identified in both libraries. It is noteworthy that an analysis of target genes showed that Cardinium-responsive miRNA-regulated genes were functional in apoptosis, reproduction, development, immune response, thermotolerance and insecticide resistance. GO and KEGG pathway analysis revealed that some miRNA-target genes are closely associated with energy metabolism. A major finding of this study was the identification of several miRNAs that may be involved in physiological processes in response to environmental stress, i.e., insecticides and high temperatures. This information will provide a foundation to help further elucidate the functions of Cardinium in B. tabaci Q.